2021
DOI: 10.21203/rs.3.rs-513568/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patient and caregiver perspectives on a tool to identify undiagnosed dementia: A qualitative study

Abstract: BACKGROUND Early detection of dementia may improve patient care and quality of life, yet as many as half of patients are undiagnosed. Electronic health record (EHR) data could potentially be used to help to identify patients at risk of having undiagnosed dementia who could be targeted for outreach and assessment, but acceptability to patients and caregivers is unknown. METHOD We conducted five focus groups at Kaiser Permanente Washington, an integrated healthcare system in Washington State, to explore feelings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Similar findings have been reported in other qualitative studies evaluating undiagnosed CI and dementia in the general population, and studies regarding other ageing‐related morbidities such as frailty among PWH [13]. Palazzo et al [12] found that older adults broadly support an early diagnosis of CI, perceiving the benefits to include time to adjust and plan for the future and to identify resources to assist in clinical management. Additionally, in their qualitative work, participants emphasized the need for thoughtful communication and that a conversation on CI should include advice on prognosis, treatment and resources if CI or dementia were diagnosed.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Similar findings have been reported in other qualitative studies evaluating undiagnosed CI and dementia in the general population, and studies regarding other ageing‐related morbidities such as frailty among PWH [13]. Palazzo et al [12] found that older adults broadly support an early diagnosis of CI, perceiving the benefits to include time to adjust and plan for the future and to identify resources to assist in clinical management. Additionally, in their qualitative work, participants emphasized the need for thoughtful communication and that a conversation on CI should include advice on prognosis, treatment and resources if CI or dementia were diagnosed.…”
Section: Discussionsupporting
confidence: 76%
“…Palazzo et al [12] found that older adults broadly support an early diagnosis of CI, perceiving the benefits to include time to adjust and plan for the future and to identify resources to assist in clinical management. Additionally, in their qualitative work, participants emphasized the need for thoughtful communication and that a conversation on CI should include advice on prognosis, treatment and resources if CI or dementia were diagnosed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation